The impact of ownership structure on earnings quality: Evidence from Chinese listed firms - Yang, Hang (2016)
The main objective of this paper is to assess the influence of ownership structure on earnings quality in China from 2007 to 2014. As an expansion of previous researches, this paper combines two research perspectives from Wang and Yung (2011) and Firth et al. (2007) and in addition, the direction of earning management is tested for detecting managerial behavior. During the analysis, I divide all Chinese listed firms into two groups at first, State-owned Enterprises (SOEs) and non-SOEs. I find that even the related party transactions are considered, SOEs are still have higher earnings quality than its counterparts, and the divergence between those two groups are growing. Then, in order to discuss into more details about the impact of different types of SOEs, SOEs are classified by their nature, which are SOEs affiliated to central government (SOECG) and other SOEs, referred as non-SOECG. The results follow the general awareness that SOECGs would have less earnings management due to facing more strict supervision and less managerial compensation incentives.